Incidence of the postpartum diagnosis of thyroid eye disease in relation to thyroid function in Graves’ disease - Nami Suzuki; Jaeduk Yoshimura Noh; Ai Kozaki; Natsuko Watanabe; Ai Yoshihara; Miho Fukushita; Masako Matsumoto; Hideyuki Imai; Shigenori Hiruma; Masahiro Ichikawa; Masakazu Koshibu; Akiko Sankoda; et al. (Endocrine Journal)
It has been reported that Graves’ disease (GD) sometimes improves spontaneously during pregnancy, although exacerbation of GD during postpartum period or relapse of hyperthyroidism caused by GD might occur. This study aimed to investigate the incidence of postpartum diagnosis of thyroid eye disease (TED) in relation to thyroid dysfunction. This retrospective cross-sectional study enrolled 11,104 deliveries from the patients with GD between January 2004 and August 2022. Within the 12-month postpartum period, 72 patients (0.65%) were diagnosed with TED. The thyroid function of the 72 patients comprised 9 remission, 13 continued antithyroid medicine, and 50 thyroid dysfunction; 30 newly diagnosed GD, 1 hypothyroidism, and 19 relapse/recurrence of GD. In the 49 patients with thyroid dysfunction, no difference was observed in the median values of thyroid-stimulating hormone (TSH) receptor antibody (TRAb) and TSH receptor stimulating antibody between the TED diagnosis and the development of hyperthyroidism. However, when the patients were classified into the newly developed GD and relapse/recurrence of GD groups, the difference became significant and the TRAb level was high in the newly developed GD (16.1 vs. 5.0 IU/L, p < 0.0001, and 15.0 vs. 6.0 IU/L, p = 0.0003). Thyroid dysfunction preceded TED diagnosis in more than half of the patients and the median time for each event was 6.5 vs. 8.1 months. The active phase TED was observed in 8 of the 72 patients. Of the 72 patients newly diagnosed with TED in postpartum, two-thirds were accompanied by thyroid dysfunction and 8 of them were in active phase.